A self-healing flexible urea-g-MWCNTs/poly(urethane-sulfide) nanocomposite for sealing electronic devices. Issue 2 (9th December 2019) - Yan, Qiming; Fu, Qi; Hu, Jianfeng; Fu, Heqing
Abstract : With the development of flexible electronic devices, strict requirements for sealing these electronics are put forward. Abstract : With the development of flexible electronic devices, strict requirements for sealing these electronics are put forward. Developing flexible sealants for next generation flexible electronic devices is essential for enabling a broad range of applications. Herein, we demonstrate a facile way to prepare a self-healing flexible urea-grafted multi-walled carbon nanotube/poly(urethane-sulfide) nanocomposite with robust mechanical strength, flexibility and high self-healing efficiency. On the one hand, urea-grafted multi-walled carbon nanotubes (urea- g -MWCNTs) are used as physical cross-linking agents, which will improve the mechanical strength and self-healing properties of the urea- g -MWCNTs/poly(urethane-sulfide) (U-MWC-PUS) nanocomposite. On the other hand, urea- g -MWCNTs act as a photothermal switch, which will absorb near-infrared (NIR) irradiation and convert it into thermal energy for local self-healing. Owing to the [2+1] radical-mediated disulfide exchange reaction and hydrogen bonding interactions in the U-MWC-PUS nanocomposite, covalent polymer networks can rearrange under thermal stimulation, which endows the U-MWC-PUS nanocomposite with self-healing properties. When the cracked U-MWC-PUS nanocomposite is kept at an appropriate temperature or treated with NIR irradiation, it can recover more than 90% of the original mechanical strength. At the same time, the self-healing mechanism of the flexible U-MWC-PUS nanocomposite was analyzed. Furthermore, the self-healing flexible U-MWC-PUS nanocomposite exhibits excellent adhesion and sealability in water. Our study may provide a facile way to fabricate self-healing flexible U-MWC-PUS nanocomposites for sealing electronic devices.